CHARACTERISTICS OF CYTOMEGALOVIRUS-INDUCED LIVER DAMAGE IN CHILDREN AT THE CENTRAL PEDIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the clinical and subclinical characteristics of liver damage in childrendue to Cytomegalovirus infection and comment on the results of treatment of liver damage inchildren due to Cytomegalovirus infection at Central Children's Hospital.Research object and method: Retrospective study - prospective study, describing over 70pediatric patients 1-12 months diagnosed with liver damage caused by Cytomegalovirus andtreated at Central Children's Hospital in the period from 01/01/2020 – 30/06/2022.Result: 70 patients with CMV liver injury were followed for 6 months with the followingratios: Mean age of patients was 2.17 ± 1.77 months, and men accounted for 84.3%, jaundice85.7%, enlarged liver 67.1%, silver stool 54.3%, dark urine 47.1%, subcutaneous hemorrhage5.7%. Alanine aminotransferase and aspartate aminotransferase both increased in all patients.Billirubin directly increased by 91%. 50/70 (71.4%) patients were treated with ganciclovir. Theimprovement in liver injury was 87.1% and no complications accounted for 87.1%.Conclusion: Most patients have good results after treatment. However, it is necessary to detectand treat in time to limit the severe damage caused by CMV.
Keywords: Liver damage, Cytomegalo virus.